Diffusion kurtosis imaging biomarkers associated with amelioration of neuroinflammation, gray matter microstructural abnormalities, and gut dysbiosis by central thalamic deep brain stimulation in autistic -like young rats - Lalitha Palanivelu; You-Yin Chen; Yao-Wen Liang; Ssu-Ju Li; Ching-Wen Chang; Yu-Ting Huang; Yu-Chun Lo (NeuroImage)
Autism spectrum disorder (ASD) is a neurodevelopmental condition characterized by abnormalities in brain microstructure, neuroinflammation, and social behavior deficits. In addition, children with ASD frequently exhibit irritable bowel syndrome and other gastrointestinal symptoms linked to anxiety. This study investigated if central thalamic nucleus deep brain stimulation (CTN-DBS) can improve social behavior, suppress neuroinflammation, restore brain microstructure, and reverse gut dysbiosis in the valproic acid-induced rat model of ASD by modulating the microbiota–gut–brain (MGB) axis. Daily CTN-DBS for 7 days (30 min/day) enhanced neuronal density, organization, and microstructural complexity as evidenced by increases in the diffusion kurtosis imaging (DKI) metrics—mean kurtosis (MK), axial kurtosis (AK), and radial kurtosis (RK). These neurostructural improvements were associated with reduced astrocyte and microglial activation, two core hallmarks of neuroinflammation in ASD, and lower systemic levels of the pro-inflammatory cytokines interleukin (IL)-1β, IL-6, interferon (IFN)-γ, and tumor necrosis factor (TNF)-α, signaling factors that may increase gut permeability and disrupt gut microbial composition. Indeed, CTN-DBS enhanced gut barrier function, promoted the proliferation of beneficial Bacteroides spp., and improved short-chain fatty acid (SCFA) metabolism, thereby restoring normal gut acetate and butyrate levels and counteracting dysbiosis. Specific energy absorption rate and thermal effect analyses demonstrated that CTN-DBS is safe under DKI. These findings support CTN-DBS as a safe and efficacious therapeutic strategy to reduce neuroinflammation, restore gray matter circuit function, and improve gut microbial composition in ASD via MGB axis modulation. Furthermore, DKI can reveal neurobiomarkers indicative of these improvements in ASD model rats.